2014
DOI: 10.1016/j.jtcvs.2013.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical and angiographic outcomes after robotic-assisted coronary artery bypass surgery

Abstract: Robotic-assisted coronary artery bypass grafting is an effective alternative to traditional coronary artery bypass grafting for patients with single or multivessel coronary artery disease, with comparable short-term clinical and angiographic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 19 publications
5
66
2
1
Order By: Relevance
“…After exclusion of duplicated studies and 546 irrelevant articles based on abstracts and titles, 126 studies remained for full-text evaluation. Of these, 44 studies met the inclusion criteria, including nine studies in the TECAB off-pump group (10)(11)(12)(13)(14)(15)(16)(17)(18); two studies in the TECAB on-pump group (19,20); and 16 studies in the robotic MIDCAB group (10,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). One study provided separate data for both the TECAB offpump and robotic MIDCAB groups, and was included for analysis in both groups (10).…”
Section: Resultsmentioning
confidence: 99%
“…After exclusion of duplicated studies and 546 irrelevant articles based on abstracts and titles, 126 studies remained for full-text evaluation. Of these, 44 studies met the inclusion criteria, including nine studies in the TECAB off-pump group (10)(11)(12)(13)(14)(15)(16)(17)(18); two studies in the TECAB on-pump group (19,20); and 16 studies in the robotic MIDCAB group (10,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). One study provided separate data for both the TECAB offpump and robotic MIDCAB groups, and was included for analysis in both groups (10).…”
Section: Resultsmentioning
confidence: 99%
“…Recent long-term follow-up studies [8,9] showed an equivalent result in terms of mortality, major adverse cardiovascular events, and need for revascularization between robotic and conventional CABG. More encouragingly, robotic CABG is likely to reduce postoperative complications in patients with single-vessel disease [18].…”
Section: Commentmentioning
confidence: 99%
“…Both left and right internal mammary arteries (IMAs) could be harvested on the same side of a patient [7]. Recent reports showed that robotic CABG had comparable short-term results to conventional CABG and a lower reintervention rate compared with percutaneous coronary intervention (PCI) [8,9]. However, report on the longterm outcome and the graft patency after robotic CABG was limited [10].…”
mentioning
confidence: 99%
“…The LIMA is then harvested according to surgeon preference, either in a skeletonized or pedicled fashion. Next, a thoracotomy is made directly over the LAD, through which the anastomosis is carried out similar to the MIDCAB procedure (robotic assisted) (9). An alternative is total endoscopic coronary artery bypass (TECAB).…”
Section: Interventionsmentioning
confidence: 99%